2019
DOI: 10.1149/2.0321901jes
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Copper Filling of Millimeter Size Through Silicon Vias

Abstract: This work demonstrates void-free Cu filling of millimeter size Through Silicon Vias (mm-TSV) in an acid copper sulfate electrolyte using a combination of a poloxamine suppressor and chloride, analogous to previous work filling TSV that were an order of magnitude smaller in size. For high chloride concentration (i.e., 1 mmol/L) bottom-up deposition is demonstrated with the growth front being convex in shape. Instabilities in filling profile arise as the growth front approaches the free-surface due to coupling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…Experimental deposition of Cu in substantially larger (125 μm diameter and 625 μm deep) through-silicon vias has established that convective transport can greatly impact feature filling, affecting not only the dynamics of the superconformal filling process but even the symmetry of the growth surface. 45 , 70 Full computational fluid dynamic calculations must be added to electrodeposition models in order to quantitatively capture how convective transport impacts deposition in larger features. Nevertheless, simulations using a fixed boundary layer provide a foundation for modelling filling in S-NDR based systems, with coupled fluid dynamics to be explored in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental deposition of Cu in substantially larger (125 μm diameter and 625 μm deep) through-silicon vias has established that convective transport can greatly impact feature filling, affecting not only the dynamics of the superconformal filling process but even the symmetry of the growth surface. 45 , 70 Full computational fluid dynamic calculations must be added to electrodeposition models in order to quantitatively capture how convective transport impacts deposition in larger features. Nevertheless, simulations using a fixed boundary layer provide a foundation for modelling filling in S-NDR based systems, with coupled fluid dynamics to be explored in the future.…”
Section: Resultsmentioning
confidence: 99%
“…2,8,9,75 For larger TSVs, 125 μm in diameter and 625 μm deep, the convex shape is even more pronounced. 77 A trend toward ⟨110⟩ texture develops normal to the active growth front, reflecting the influence of Cl − on the polymer-disrupted and/or -denuded growth surface. 76 Models based on transport-constrained suppressor motion and consumption, Figure 9, can capture the general bottom-up filling behavior based on additive consumption.…”
Section: Leveler−accelerator Interactionsmentioning
confidence: 99%
“…The same dynamics apply to larger 125-μm-diameter and 625-μmdeep vias, with Cl − consumption and depletion determining the location and shape of the passive−active sidewall transition. 77 Importantly, given the passive−active transition, filling of the vias requires decreasing the applied potential to more negative values to move the transition and associated active deposition upward but is slow enough that Cu 2+ depletion does not result in void formation. Simulations, including forced hydrodynamics in the 625-μm-deep vias, capture the observed evolution of the growth front geometry and filling trends, although a more detailed comparison of filling in these largest vias awaits experiments with well-defined hydrodynamics.…”
Section: Leveler−accelerator Interactionsmentioning
confidence: 99%
“…[25] In our prior work with Electrifi on PLA substrates, [22] it was demonstrated that adding organic additives had a pronounced effect on reducing the resulting surface roughness. [26][27][28] Furthermore, while not specifically demonstrated here, levelers can also be used in other plating baths such as nickel. After plating for 8 h, the plating resulted in a shiny and far more polished looking appearance.…”
Section: Doi: 101002/admt201900126mentioning
confidence: 99%
“…Since smoother metal films can be obtained by filling concave gaps between the thermoplastic lines, additives used for Cu metallization in semiconductor and PCB processes can further improve the surface morphology of the electroplated films. [26][27][28] Furthermore, while not specifically demonstrated here, levelers can also be used in other plating baths such as nickel. [28] The electroplating process here is suitable for integration with electronics.…”
Section: Doi: 101002/admt201900126mentioning
confidence: 99%